PLAGUE BEHIND GARRISON WALLS: SYPHILIS, GONORRHEA, AND REPRODUCTIVE HEALTH CRISES IN 19TH-CENTURY SULAWESI - Lucia Arter Lintang Gritantin; Krida Amalia Husna (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This article examines the venereal disease epidemic that swept through Sulawesi during the nineteenth century as a structural consequence of Dutch colonial military expansion. Drawing on colonial military medical reports, residency archives from Makassar and Manado, periodic medical journals, and missionary diaries, the study argues that the garrison complexes of the Koninklijk Nederlandsch-Indische Leger (KNIL) functioned as the primary epidemiological epicentres for the diffusion of syphilis (Treponema pallidum) and gonorrhoea (Neisseria gonorrhoeae) into civilian populations. Three interconnected processes are identified: first, the hyper-masculine demographic concentration within garrison walls that generated commercial and institutionalised sexual economies; second, the high spatial mobility of troops that transformed localised outbreaks into territory-wide transmission networks; and third, the systematic exclusion of indigenous women from meaningful therapeutic care. The evidence demonstrates that preantibiotic era infection produced a mass reproductive health crisis among local women, manifesting as secondary infertility, spontaneous abortion, stillbirth, and congenital syphilis. Colonial biopolitical responses compulsory registration, coercive hospitalisation, and mercury based treatment further imperilled women’s bodies rather than safeguarding them. The article also recovers subaltern forms of resistance, including flight to the interior, bribery of health officers, and identity falsification, which challenged the colonial apparatus of bodily control.